REE and Gallium in the diasporite deposits of Mikri Lakka, east Samos Island, Greece - Stamatakis, Michael; Koltiri, Alexandra (Bulletin of the Geological Society of Greece, 2025)
In Samos Island, Aegean Sea, Greece, several diasporite and emery occurrences and idle mines occur. The major diasporite deposit is developed at the eastern part of the island at Mourtia, Mikri Lakka where there exist old mining works. The specific metabauxite is hosted, via a transition zone, in between marble of Mesozoic age which has been tectonically disturbed. The aim of the present study is to characterize the metabauxite deposit and to investigate its content in specific trace elements and especially REE and gallium. XRD, XRF and SEM-EDS analysis carried out in representative samples of the massive diasporite deposit, the transition zone and the associated marble. XRD analysis revealed that the marble is calcitic. The transition zone is mainly composed of muscovite, illite, kaolinite, quartz and calcite with minor amounts of diaspore, whereas the main ore body is composed mainly of diaspore, followed by minor-trace amounts of calcite, muscovite, magnetite, hematite and quartz. XRF major element analysis has shown that the ore body is rich in alumina and secondarily in iron oxides. The trace element analysis discloses a notable enrichment in Ga, some REE and zirconium. Gallium is not detected by SEM-EDS as any gallium mineral, and it is most likely being fixed in the lattice of diaspore. It is concluded that the derivation of all trace elements enrichments and the source of alumina from the Mesozoic rocks of the Ampelos Nape, which included originally sedimentary rocks, gabbro and volcanics. These rocks were weathered and altered under wet conditions releasing silica, alumina and iron, which formed bauxite deposits rest on a limestone substrate. Finally, the limestone-bauxite succession was metamorphosed and tectonically disturbed. Concerning the economic importance of the Mikri Lakka diasporite, it is noted that bauxite/diasporite deposits have a potential of hosting significant REE concentrations. The average gallium content of the Mikri Lakka massive diasporite is 79 ppm (max of 96 ppm), which is higher than the average gallium content of the bauxite deposits and occurrences of Parnassus-Ghiona-Oiti Greece. Both the REE and gallium content of the Mikri Lakka diasporite is promising to consider their recovery as byproducts during diasporite exploitation, despite the fact that its proven reserves in the east part of Samos are unknown.